Principais obstáculos enfrentados pela agricultura familiar para sua participaç\~ao no plano ABC+ - Júnia Cristina Péres Rodrigues da Conceiç\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of this work was to analyze the process of inclusion of family farming in the ABC+ Plan. Initially, a historical contextualization of the emergence of the ABC Plan was made. Little participation of family farming in this Plan was verified. With the emergence of the ABC+ Plan, which is the second stage of the plan, there was a perception that it would be a good strategy for family farming to be included. The limitations for the inclusion of family farmers in the Plan refer to the challenges faced by these farmers in their insertion in the agricultural policy in general. Finally, actions are needed to actually cause the explicit inclusion of family farming in the policies for mitigating and adapting to climate change, provided for the ABC+ Plan.
Keywords: Q; Q01; 330; family farming; ABC+ Plan; sustentability